Historic Institutionalism and Urban Morphology in Jakarta: Moving Towards Building Flood Resiliency into the Formal Planning and Development System - David Wallace Mathewson (The Institute for Research and Community Services, Institut Teknologi Bandung, 2018)
This paper examines issues around flooding and rapid urban development in Jakarta, specifically the manner in which the former has influenced the spatial growth of the city over time. It takes a historic-institutionalism perspective within the context of changing government responses to flood management, where previous approaches failed to take into consideration existing local ecology, flood patterns and natural drainage systems. Jakarta is slowly moving towards more sustainable and resilient approaches to flood management through pilot programmes aimed at reclaiming or restoring water bodies while creating urban green space to assist with water absorption, despite the local government not having incorporated sustainable flood management systems or mitigation measures into the formal planning system. This paper shows how flooding has influenced spatial development and urban morphology in the city historically, which has led the city administration to the realisation that new approaches are required. The methodology includes document and literature research, GIS as well as satellite based mapping and imagery to determine spatial development patterns and where additional mitigation measures may be required, as well as flooding and drainage documentation. The paper reveals a series of potential strategies for the initial stages of planning policy implementation and a potential framework for developing planning-incorporated measures at a wider scale across Jakarta's affected areas. This study has wide implications for a number of large developing cities in the Global South that face multiple development challenges in addition to flooding.Keywords. Historic institutionalism, urban morphology, flood resiliency, urban planning.Abstrak. Makalah ini mengkaji isu-isu seputar banjir dan pembangunan perkotaan di Jakarta yang cepat, khususnya bagaimana fenomena banjir mempengaruhi pertumbuhan spasial kota dari waktu ke waktu. Dibutuhkan perspektif historis-institusionalisme dalam konteks perubahan respons pemerintah terhadap manajemen banjir, yakni ketika pendekatan sebelumnya gagal mempertimbangkan ekologi lokal yang ada, pola banjir dan sistem drainase alami. Jakarta perlahan bergerak menuju pendekatan manajemen banjir yang lebih berkelanjutan dan tangguh melalui program percontohan yang bertujuan untuk merebut kembali atau memulihkan badan air sambil menciptakan ruang hijau perkotaan untuk membantu penyerapan air meski pemerintah daerah belum memasukkan sistem manajemen banjir berkelanjutan atau langkah-langkah mitigasi ke dalam sistem perencanaan formal. Makalah ini menunjukkan bagaimana banjir telah mempengaruhi perkembangan ruang dan morfologi perkotaan di kota secara historis yang telah menyebabkan pemerintah kota untuk menyadari akan perlunya pendekatan baru. Metodologi makalah mencakup penelitian dokumen dan literatur, pemetaan dan citra berbasis GIS dan satelit untuk menentukan pola pengembangan ruang apabila langkah-langkah mitigasi tambahan mungkin diperlukan, serta dokumentasi banjir dan drainase. Makalah ini mengungkapkan serangkaian strategi potensial untuk tahap awal implementasi kebijakan perencanaan dan kerangka potensial untuk mengembangkan langkah-langkah yang memasukkan perencanaan pada skala yang lebih luas di seluruh wilayah yang terkena dampak di Jakarta. Studi ini memiliki implikasi luas bagi sejumlah kota besar yang berkembang yang menghadapi berbagai tantangan pembangunan selain banjir.Kata Kunci. Institusionalisme historis, morfologi perkotaan, ketahanan banjir, perencanaan kota.